(untitled) (TEST Trento Student Law Review, 2024)
The European Union (EU), in the continuous effort to assert itself as a global regulatory power, is attempting to regulate Corporate Sustainability Due Diligence through a Directive proposed by the European Commission in February 2022 (CSDDD), and currently under consideration by the co-legislators. Such Proposal envisages obligations for both EU and non-EU companies falling under its personal scope to identify, mitigate, and bring to an end all adverse effects to human rights and sustainability arising out of the company’s own operations, its subsidiaries, and value chain regardless of the location, pending sanctions and civil liability in the EU. Given the far-reaching obligations regulating conduct abroad, it is essential to ascertain whether the EU is engaging in a lawful exertion of extraterritorial jurisdiction, or if the CSDDD Proposal would be too far of a jurisdictional encroachment into other States’ sovereignty. After reviewing the relevant triggers of application of the Directive both under international and EU law, it is submitted that the Proposed Directive does not appear to be manifestly violating international law, without prejudice to discussions on the current amendments in the course of the ordinary legislative process.